Factors that affect the activeness of the elderly in participating in prolonged gymnastics in patients with hypertension - Muh.Ihsan Kamaruddin (Edukasi Ilmiah Indonesia, 2023)
Hypertension is a health problem often encountered in the elderly, and Prolanis gymnastics has proven beneficial in controlling blood pressure and improving their quality of life. This study aims to identify factors that affect the activeness of the elderly in participating in Prolanis gymnastics (Program for the Elderly with Hypertension) as part of efforts to manage hypertension. Quantitative research is based on the philosophy of positivism with analytical research design with a Cross-Sectional study design approach. The results of the Chi-square Statistical test on the influence of knowledge, attitudes, and motivation on the participation of older adults with hypertension in prolantic gymnastics activities obtained p-values = 0.003, 0.000, and 0.000 smaller than a = 0.05. It can be concluded that knowledge, attitudes, and motivation influence the activeness of older adults with hypertension in prolantic gymnastics activities. The results of this study provide valuable insights into how to move older adults with hypertension to participate more actively in the Prolanis gymnastics program. With the right knowledge, attitude, and motivation, it is hoped that the participation of the elderly in health programs can increase, which in turn will contribute to better management of hypertension and improvement of their quality of life.